Problems in Enforcing the Liquor Prohibition Regulation - Wahib, Moh.; Rohman , Baitur; Irawati, Dewi (Syarah: Jurnal Hukum Islam dan Ekonomi, 2025)
Enforcing local regulations prohibiting alcoholic beverages in Papua is a complex challenge that requires a comprehensive understanding of the legal framework, law enforcement practices, and community dynamics. This study aims to analyze the challenges of enforcing the prohibition of alcoholic beverages in Papua Province. The researcher seeks to explore the substance of the prohibition of alcoholic beverages in Papua Regulation No. 15 of 2013 and its legal status within the Indonesian legal framework. The results of the study reveal that the substance of Papua Regulation No. 15 of 2013 is to completely ban the production, distribution, sale, and consumption of alcoholic beverages. This legal status is legally contrary to the principle of the hierarchy of laws based on the principle of "Lex Superiori Derogad Lege Inferiori." This Regional Regulation was revoked by the Minister of Home Affairs via Letter No. 188 34-3629 of 2016. However, to protect the public from the negative impacts of alcoholism, the Governor of Papua continued to enforce the Regional Regulation. The Governor of Papua, from a progressive legal perspective, has set aside the principle of legal certainty for the sake of humanity; however, within the context of a rule-of-law state, this violates the principle of "due process of law."